Health belief model-based intervention on knowledge and practice of standard precautions among primary healthcare workers in a state of Malaysia - Ramlan, Waramlah; Zainuddin, Huda (Southeast Asian Ministers of Education Organisation, 2020)
The Standard Precautions (SP), which consists of hand and respiratory hygiene, personal protection equipment, safe injection and others are crucial in preventing healthcare-associated infections (HAIs) and occupational infections among healthcare workers (HCWs). HAIs have caused antimicrobial resistance, increase mortality and financial burden to the health organization. Europe has shown 40.8% compliance to SP while in Malaysia, only 50% of HCWs comply with SP. Health Belief Model (HBM)-based intervention was developed to promote behavioural change among HCWs. This research aims to evaluate the effectiveness of HBM-based intervention module in improving knowledge and practice of SP among HCWs. This is a cluster randomized control trial involving 104 HCWs in the control group and 94 HCWs in the intervention group from eight health clinics in a state in Malaysia. The scores of knowledge and practice were computed using a self-administered questionnaire at pre-, immediate post- and 6-months post-intervention. The intervention group was given a one-day intervention course while the control group had received the same intervention after the study completed. Analysis showed that there was a significant difference in knowledge and practice scores between and within groups after adjusting for covariate and cluster effect (p<0.05). All HBM constructs also demonstrated significant improvement (p<0.05) between and within groups except for the perceived barrier (p=0.813 and p=0.931 respectively). The intervention module is effective in improving the knowledge and practice of SP among HCWs. Regular and periodic educational training incorporated with HBM is essential to promote behavioural change.